Sexual Dimorphism of Greater Sciatic Notch among Nepalese Population by Three Dimensional CT Images of Pelvis - Karki, R. K.; Bhandari, R.; Karki, S.; Shah, D. K. (Kathmandu University Medical Journal, 2020)
Background Sex identification from the skeletal remains, is the first and the foremost step encountered by forensic experts. Hip bone being comparatively robust is resistant to damage and scores even in improperly preserved skeletons. It is also widely agreed that the greater sciatic notch (GSN) holds the greatest degree of sexual dimorphism. Objective To study the role of greater Sciatic Notch parameters in sex determination among Nepalese population by means of reconstructed Multi Slice Three-Dimensional Computed Tomography (MDCT) images. Method The CT images of individuals who underwent pelvic CT in the Department of Radiology, Dhulikhel Hospital were included in the study. Measurements of width, depth, angles and indices of greater sciatic notch were measured and calculated. Data were entered and analyzed using SPSS (Statistical Package for Social Sciences) version 25.0. Result There was a significant difference between means of all greater sciatic notch parameters (p > 0.001) between sex showing sexual dimorphism except depth (p=0.65). By using limiting point, 78.18% male and 83.64% female were correctly classified by using total width. Total angle, Posterior segment and Total width had sensitivity and specificity exceeding 80% and overall accuracy of 87% to 92% in all parameters except depth by receiver-operator characteristic curve analysis. Conclusion Application of 3D-CT virtual images in the present study helped us to easily quantify greater sciatic notch parameters. The important greater sciatic notch predictors for sex determination in Nepalese population were determined which would help forensic experts in ascertaining the sex of an unknown individual.